Exercise or else : how goal framing and language tone affect exergame messaging via psychological reactance. - Subramaniam, Aneesha. (2013)
Obesity rates amongst youths and adolescents is on an upward trajectory, prompting calls by academics and policymakers to implement media and school-based interventions. Recent advances in intervention programming revolve around exercise-based video games, or exergames. These games have been shown to enhance physical activity attitudes and behaviours in children and adolescents when incorporated into physical education lessons. Health communication literature is replete with evidence that variables such as goal framing and language tone can affect the effectiveness of messaging in persuasion. This study aims to determine if goal framing and language tone in instructional material can affect message persuasiveness through psychological reactance, hence impeding the effectiveness of such programmes. An intervention programme utilizing a 2 x 2 design was employed on international students between the ages of 10 and 19 in Singapore. Results showed that loss-framing and dogmatic language are two of the message features that can trigger perceived threats to freedom and state reactance. This can potentially lead to boomerang effects in attitudes and behaviours encouraged by such health promotional messaging. Implications on intervention programming and other obesity-specific health campaigns are discussed.